Immersive encounters: video, swimming and wellbeing. Issue 1 (1st January 2023) - Bates, Charlotte; Moles, Kate
Abstract : Using a GoPro harnessed to the body of participants, we sent the camera into the sea, in order to explore how swimming under an open sky makes people feel about themselves and the natural world. Giving people GoPro cameras to record their swims and make pre- and post-swim video diaries, we aimed to investigate the rejuvenating effects of cold water and the connections between swimming and wellbeing. We are interested in the ways in which wellbeing is experienced, understood, and constructed in situ as an unfolding event. Here, we reflect on the methodological challenge of conducting research on the move and in water. We suggest that the technological innovation of the GoPro, a lightweight, small, rugged and, most essentially for us, waterproof camera, provides new means of addressing methodological challenges, while the combination of this technology with the video diary method enables the development of a multidimensional and multisensory account that mixes together talk and action, helping us to develop more immersive and attentive ways of doing research through which we can come to understand different ways of being in the water.